2014
DOI: 10.1128/mcb.01011-13
|View full text |Cite
|
Sign up to set email alerts
|

p53 Tumor Suppressor Protein Stability and Transcriptional Activity Are Targeted by Kaposi's Sarcoma-Associated Herpesvirus-Encoded Viral Interferon Regulatory Factor 3

Abstract: cViruses have developed numerous strategies to counteract the host cell defense. Kaposi's sarcoma-associated herpesvirus (KSHV) is a DNA tumor virus linked to the development of Kaposi's sarcoma, Castleman's disease, and primary effusion lymphoma (PEL). The virus-encoded viral interferon regulatory factor 3 (vIRF-3) gene is a latent gene which is involved in the regulation of apoptosis, cell cycle, antiviral immunity, and tumorigenesis. vIRF-3 was shown to interact with p53 and inhibit p53-mediated apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…LANA2 inhibits both the transcriptional activation and apoptosis induced by p53 through the inhibition of p53 phosphorylation, by altering its oligomerization and DNA-binding affinity, and by increasing its polyubiquitylation. [3][4][5][6][7][8] Apart from p53, LANA2 also compromises the activity of other tumor suppressors such as pRb or PML. 9,10 Interestingly, the control of these 2 tumor suppressors by LANA2 involves the regulation of their SUMO conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…LANA2 inhibits both the transcriptional activation and apoptosis induced by p53 through the inhibition of p53 phosphorylation, by altering its oligomerization and DNA-binding affinity, and by increasing its polyubiquitylation. [3][4][5][6][7][8] Apart from p53, LANA2 also compromises the activity of other tumor suppressors such as pRb or PML. 9,10 Interestingly, the control of these 2 tumor suppressors by LANA2 involves the regulation of their SUMO conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that KSHV regulates host gene expression by expressing several viral genes, including vIRF3, vIRF7, and the gene for a viral protein kinase (ORF36) (12,33). To understand how ANGPT-1 was upregulated in KSHV-infected PEL cells and how KSHV contributed to ANGPT-1 gene expression, we constructed ANGPT-1 promoter-luciferase reporter constructs (Ϫ898 to ϩ490 of Luc, where ϩ1 is the transcription start site and ϩ490 is the A in ATG, the ANGPT-1 translation initiation codon) and measured their transcriptional activity.…”
Section: The Luciferase Activity Of the Regulatory Region Of Angpt-1 mentioning
confidence: 99%
“…These latency-related viral products may also be involved in enhancement of the expression of various cytokines and growth factors, such as angiopoietin-1 (ANGPT-1), ANGPT-2, vascular endothelial growth factor (VEGF), interleukin-6 (IL-6), IL-8, and tumor necrosis factor alpha (6,(25)(26)(27)(28)(29). The angiogenic and inflammatory cytokines regulated by viral proteins or KSHV infection could lead to the induction of lymphangiogenesis, angiogenesis, and antiapoptosis and likely play an important role in KSHV pathogenesis (12,26,(30)(31)(32)(33).In a previous study, we compared the gene expression profiles of KSHV-infected BC1, BCBL1, and BC3 cells with those of uninfected Daudi, AKATA, Raji, Ramos, and Namalwa cells and MT4, SupT1, Jurkat, and Molt3 leukemia cells. We found that ANGPT-1, a proangiogenic and proinflammatory cytokine, was expressed at significantly higher levels only in KSHV-infected PEL cells (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations